Study on Catastrophe Instability of Support System in Gypsum Goaf Based on Energy Dissipation Theory. (4th December 2018) - Zhou, Yuejin; Xu, Xiaoding; Li, Xiaotong; Li, Meng; Yang, Yugui
Abstract : The stability of the goaf support system is the key to safe production in gypsum mines. Therefore, this study constructed a pillar-beam support system which contained pillar plastic zones. In this support system, the beam and pillar were taken as energy releaser and energy dissipater, respectively. Through establishing a cusp catastrophe model based on energy theory, the new criterion for instability was obtained which is related with geometric stiffness and system energy dissipation. The results indicate the instability of the support system is caused by the incompatibility of energy release, dissipation, and geometric deformation. When K > 1, the energy released by the support system is compatible with geometric deformation. The support system experiences a quasistatic process from the static state in bottom page to the static state in top page along Path I. When K < 1, the energy released by the support system cannot be in tune with geometric deformation. The support system experiences a catastrophe process along Path II. The evolution from the static state in bottom page to the static state in top page is not progressive, but catastrophic. The redundant energy released in this process leads to mechanical instability of the support system. This study provided theoretical foundation for the mining and treatment of mines. Based on actual engineering examples, the sensitivity of the geometric parameters of the support system was analyzed as well. These parameters are ranked by their sensitivity from high to low, as is shown below: beam thickness, plastic zone width, room span, pillar width, and pillar height. Then, the goaf was classified according to the geometric parameters. Energy catastrophe theory was applied to analyze the stability of the support system in different classes of goaf. The analysis results showed that Class D goaf should be labeled as the unstable zone, which was consistent with the result of field research. To conclude, energy catastrophe theory can be used to demonstrate the nonlinear mechanical mechanism of support system instability in room-pillar mining goaf.